2018
DOI: 10.1096/fj.201701503rr
|View full text |Cite
|
Sign up to set email alerts
|

Maternal folic acid supplementation with vitamin B 12 deficiency during pregnancy and lactation affects the metabolic health of adult female offspring but is dependent on offspring diet

Abstract: Epidemiologic studies have reported relationships between maternal high folate and/or low B status during pregnancy and greater adiposity and insulin resistance in children. The goal of this study was to determine the effects of maternal folic acid supplementation (10 mg/kg diet), with (50 μg/kg diet) and without B, on adult female offspring adiposity and glucose homeostasis. Female C57BL/6J mice were fed 1 of 3 diets from weaning and throughout breeding, pregnancy, and lactation: control (2 mg/kg diet folic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
(84 reference statements)
0
29
0
Order By: Relevance
“…27 More recently, Henderson et al reported that maternal folic acid supplementation with vitamin B 12 deficiency during pregnancy or lactation can affect the metabolic health of adult female offspring, which involves the effects of maternal diet on the β-cells of offspring. 28 Several limitations of this study should be acknowledged. First, this study was a cross-sectional observational study, and it could not prove causation of the relationship between folate and vitamin B 12 imbalance and GDM.…”
Section: Discussionmentioning
confidence: 92%
“…27 More recently, Henderson et al reported that maternal folic acid supplementation with vitamin B 12 deficiency during pregnancy or lactation can affect the metabolic health of adult female offspring, which involves the effects of maternal diet on the β-cells of offspring. 28 Several limitations of this study should be acknowledged. First, this study was a cross-sectional observational study, and it could not prove causation of the relationship between folate and vitamin B 12 imbalance and GDM.…”
Section: Discussionmentioning
confidence: 92%
“…Another likely possibility is that the fetal underdevelopment is a result of other components in the 1C imbalanced diet. Excess folate alone has previously been shown to cause placental abnormalities and embryonic defects in mice [ 20 , 21 ]. In addition, low B12 combined with high folate may exacerbate B12 deficiency [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excess folate alone has previously been shown to cause placental abnormalities and embryonic defects in mice [ 20 , 21 ]. In addition, low B12 combined with high folate may exacerbate B12 deficiency [ 21 , 22 ]. The 1C imbalanced diet contained large quantities of methionine (10,635 mg/kg diet), which has been shown to cause in poor physiological and pathological outcomes, both alone and combined with low B12 [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing concern that higher FA intakes may lead to adverse health outcomes, as intakes of 1 mg/d FA have been associated with acceleration of mammary tumors in rats [28], and colorectal [29] and prostate [30] cancer in adults. There is also evidence that excess FA intakes may have adverse effects on metabolic health during development [31,32] suggesting young children undergoing periods of rapid growth and development are especially vulnerable. The association of adverse health outcomes with high FA intake remains controversial, but debate has limited some countries from adopting mandatory nationwide FA fortification programs due to these concerns [33].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%